Metal-free cascade reactions of aziridines with arylalkynes and aryldiazoniums: facile access to arylazopyrrolines. Issue 16 (7th April 2020) - Rong, Jing; Jiang, Hao; Wang, Sijing; Su, Zhenni; Wang, Huiyan; Tao, Chuanzhou
Abstract : A novel and facile approach to synthesize arylazopyrroline scaffolds via metal-free cascade reactions of aziridines with arylalkynes and aryldiazoniums has been developed, providing access to a variety of 4-arylazo-2-pyrrolines in a highly concise fashion. Abstract : A novel and facile approach to synthesize arylazopyrroline scaffolds via metal-free cascade reactions of aziridines with arylalkynes and aryldiazoniums has been developed, providing access to a variety of 4-arylazo-2-pyrrolines in a highly concise fashion. This efficient process, which can be performed at the gram scale, enjoys operational simplicity and mild and metal-free conditions.